Heterologous Carotenoid-Biosynthetic Enzymes: Functional Complementation and Effects on Carotenoid Profiles in Escherichia coli - Song, Gyu Hyeon (American Society for Microbiology, 2013)
A limited number of carotenoid pathway genes from microbial sources have been studied for analyzing the pathway complementation in the heterologous host Escherichia coli. In order to systematically investigate the functionality of carotenoid pathway enzymes in E. coli, the pathway genes of carotenogenic microorganisms (Brevibacterium linens, Corynebacterium glutamicum, Rhodobacter sphaeroides, Rhodobacter capsulatus, Rhodopirellula baltica, and Pantoea ananatis) were modified to form synthetic expression modules and then were complemented with Pantoea agglomerans pathway enzymes (CrtE, CrtB, CrtI, CrtY, and CrtZ). The carotenogenic pathway enzymes in the synthetic modules showed unusual activities when complemented with E. coli. For example, the expression of heterologous CrtEs of B. linens, C. glutamicum, and R. baltica influenced P. agglomerans CrtI to convert its substrate phytoene into a rare product—3,4,3′,4′-tetradehydrolycopene—along with lycopene, which was an expected product, indicating that CrtE, the first enzyme in the carotenoid biosynthesis pathway, can influence carotenoid profiles. In addition, CrtIs of R. sphaeroides and R. capsulatus converted phytoene into an unusual lycopene as well as into neurosporene. Thus, this study shows that the functional complementation of pathway enzymes from different sources is a useful methodology for diversifying biosynthesis as nature does.